Risks and interrelationships of subdistrict house prices - Alfred Larm Teye; Jan de Haan; Marja Elsinga (A+BE: Architecture and the Built Environment)
This paper uses individual house transaction data from 1995 to 2014 in Amsterdam to explore the risks and interrelationships of the subdistrict house prices. Simple indicators suggest that house prices grow faster and are more risky in the central business district and its immediate surrounding areas than in the peripherals. Furthermore, we observe an over time decreasing inter-variations between the subdistrict house price growth rates, whereas we find a lead-lag and house price causal flow from the more central to the peripheral subdistricts.